ISOLASI ENZIM HORSERADISH PEROKSIDASE (HRP) DARI KULTUR SEL DAUN ARMORACIA LAPATIFOLIA DENGAN CARA FRAKSINASI MENGGUNAKAN AMONIUM SULFAT - A. T. Karossi; S Pudjiraharti (Research Center for Chemistry - LIPI, 2010)
Isolation of HRP ( Horseradish Peroksidase ) from Armoracia lapatifolia plant cell culture was conducted by fractionation using ammonium sulfate. Optimation of thefractionation process was carried out by concentrating the crude enzyme, investigating the fractionation stages and precipitation with ammonium sulfate. Two-stage fractionation namely with 0 - 40% and 40 - 85 % saturation of ammonium sulfate gave better results in terms of enzyme activity. In 0 - 40% saturation, the purity was 23fold with 11.4 %yield. The 20 highest yield, 60% and purify of 43 folds were showed by fraction which were obtained at fractionation 40 - 85 % saturation.Keyword: Horseradish Peroksidase, Annoracia Lapatifolia